Solution Of Job Sequencing In Intuitionistic Fuzzy Environment (Journal of Namibian Studies : History Politics Culture, 2023)
In this paper sequencing problem is solved with intuitionistic fuzzy numbers. Processing times taken as intuitionistic fuzzy numbers are defuzzified with defined ranking and optimal sequence is obtained. In the last total elapsed time and idle time for each machine is also calculated. Numerical example is given to clear the concept.